2015
DOI: 10.1063/1.4934993
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic substitution with two reactive centers: The CN− + CH3I case

Abstract: The nucleophilic substitution reaction CN(-) + CH3I allows for two possible reactive approaches of the reactant ion onto the methyl halide, which lead to two different product isomers. Stationary point calculations predict a similar shape of the potential and a dominant collinear approach for both attacks. In addition, an H-bonded pre-reaction complex is identified as a possible intermediate structure. Submerged potential energy barriers hint at a statistical formation process of both CNCH3 and NCCH3 isomers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 27 publications
3
42
0
Order By: Relevance
“…For F −  + CH 3 Cl dominant backward scattering of the Cl − product ion is observed with respect to the incoming CH 3 Cl velocity, while scattering into the forward hemisphere and isotropic scattering barely contribute to the velocity distribution. This backward scattering feature corresponds to the commonly assumed collinear substitution mechanism under Walden inversion and has already been reported in previous studies on this and other similar systems 8, 13, 36 . Both backward and forward scattering are present in the reaction F −  + C 2 H 5 Cl, whereby backward scattering events appear at velocities considerably lower than in F −  + CH 3 Cl, indicative of a higher degree of energy partitioning among the larger number of C 2 H 5 Cl rovibrational modes.…”
Section: Resultssupporting
confidence: 85%
“…For F −  + CH 3 Cl dominant backward scattering of the Cl − product ion is observed with respect to the incoming CH 3 Cl velocity, while scattering into the forward hemisphere and isotropic scattering barely contribute to the velocity distribution. This backward scattering feature corresponds to the commonly assumed collinear substitution mechanism under Walden inversion and has already been reported in previous studies on this and other similar systems 8, 13, 36 . Both backward and forward scattering are present in the reaction F −  + C 2 H 5 Cl, whereby backward scattering events appear at velocities considerably lower than in F −  + CH 3 Cl, indicative of a higher degree of energy partitioning among the larger number of C 2 H 5 Cl rovibrational modes.…”
Section: Resultssupporting
confidence: 85%
“…SN2 reactions are mostly studied between halide ions and methyl halides, however, over the past 30 years the variety of the analysed reactions has widened. On one hand, halide ions can be replaced with several other nucleophiles, such as OH − , SH − , CN − , NH2 − , PH2 − , etc., [19][20][21][22][23][24][25] on the other hand, methyl halides can be substituted with relevant alkyl halides. [26][27][28][29][30] For the OH − + CH3Y [Y = F, Cl, Br, I] gas-phase SN2 reactions, previous studies showed that in the product channel, instead of the traditional HOCH3•••Y − ion-dipole complex, a hydrogenbonded CH3OH•••Y − global minimum can be found.…”
Section: Introductionmentioning
confidence: 99%
“…7,11,12,15 In the present work we focus on ''rethinking'' the gas-phase X À + CH 3 Y [X = OH, SH, CN, NH 2 , PH 2 ; Y = F, Cl, Br, I] S N 2 reactions using high-level ab initio methods. Among the 20 possible fundamental S N 2 reactions with the above-defined 5 different nucleophiles (X À ) and 4 leaving groups (Y), there are only a few which were studied previously in the gas [16][17][18][19][20][21][22][23][24] and/or condensed [25][26][27][28][29] phases, and almost none of them in view of the recent non-traditional mechanisms. Focusing on the gas-phase studies, in the case of Y = F Gonzales et al 16,17 characterized 3 stationary points, i.e., pre-and post-reaction complexes and a Walden-inversion transition state, for each reaction; however, front-side complex formation, a front-side attack transition state, and double inversion were not investigated, partially due to the fact that some of these were not known at that time.…”
Section: Introductionmentioning
confidence: 99%